What drives consumers to interact with brands through social media? A motivation scale development study - Enginkaya, Ebru; Yilmaz, Hakan (ELSEVIER SCIENCE BV, 2014)
Online platforms and social networks directly influence the consumer-brand relationship. Consumption behaviours evolve in this connective world as a vital part of individuals' self-concept whereas social identities come into prominence through these online platforms. Brands, offering identity extensions and symbolic values to their customers and seeking visibility over social networks, try to create interaction and engagement with consumers via their online presence. This study was conducted to explore consumers' motivations to interact with and/or about the brands on social media and to develop a related scale. Findings of exploratory and confirmatory analyses revealed five distinct motivation factors; Brand Affiliation, Investigation, Opportunity Seeking, Conversation, and Entertainment. Comparison of these motivations and their relevancy with the consumer behaviour literature was discussed. (C) 2014 The Elsevier Ltd.
Keywords: Social media marketing; online brand engagement; consumer interaction; motivations; Business & Economics; Social Sciences - Other Topics